Kanban sharing and optimization in Bosch production system - Salgado, Pedro (2010)
Information sharing and optimization is a key factor for effective knowledge management, which is based on data exchange, communication and technological infrastructures and standardization, being essential in order to remain competitive in the today's global market scenario. In this context, human functions are also relevant, and in this work we refer to the interaction of both in the optimization of Bosch Production System. Therefore, the aim of this paper consists on presenting the minimization of kanbans, when sharing this information in a proposed cellular manufacturing environment in Bosch production, in order to enhance workflows and material and work in process management as well as human interactions and production performance and productivity.